2015
DOI: 10.1523/jneurosci.2371-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Audio-Vocal Interaction in Single Neurons of the Monkey Ventrolateral Prefrontal Cortex

Abstract: Complex audio-vocal integration systems depend on a strong interconnection between the auditory and the vocal motor system. To gain cognitive control over audio-vocal interaction during vocal motor control, the PFC needs to be involved. Neurons in the ventrolateral PFC (VLPFC) have been shown to separately encode the sensory perceptions and motor production of vocalizations. It is unknown, however, whether single neurons in the PFC reflect audio-vocal interactions. We therefore recorded single-unit activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 64 publications
2
30
0
Order By: Relevance
“…Recently, it has been shown that monkeys are able to show vocal usage learning in a well-controlled experimental design53 and that prefrontal and premotor structures might serve as potential hubs controlling such complex audio-vocal communicative behaviours5859606162. It would be interesting to see whether and how such frontal cortex circuits contribute to priming of vocal behaviour in response to social experience.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that monkeys are able to show vocal usage learning in a well-controlled experimental design53 and that prefrontal and premotor structures might serve as potential hubs controlling such complex audio-vocal communicative behaviours5859606162. It would be interesting to see whether and how such frontal cortex circuits contribute to priming of vocal behaviour in response to social experience.…”
Section: Discussionmentioning
confidence: 99%
“…Previous single-unit (Hage and Nieder 2015; Hwang and Romanski 2015; Romanski et al, 2005; Sugihara et al, 2006) and neuroimaging results (Grady et al, 2008; Rama et al, 2004; Rama and Courtney 2005; Strand et al, 2008; Zatorre et al, 1994) have suggested that ventral PFC is important for auditory processing and auditory working memory. The inactivation experiments in Plakke et al, (2015) provides direct evidence that VLPFC is an essential region for auditory working memory and suggests VLPFC is a major end point of the auditory ventral stream, necessary for auditory cognition.…”
Section: Vlpfc Is Essential For Auditory Working Memory and Audiovisumentioning
confidence: 96%
“…This stream primarily encodes auditory space. Converging auditory input in the ventro-lateral PFC (vlPFC) gives rise to neurons that respond to the spatial and nonspatial attributes of complex auditory stimuli (Cohen et al, 2004), and represent complex acoustic stimuli such as species-specific vocalizations (Romanski and Goldman-Rakic, 2002; Averbeck and Romanski, 2006; Hage and Nieder, 2015) and sound categories (Russ et al, 2007; Lee et al, 2009). …”
Section: Multisensory Innervation Of the Lateral Pfc And Premotor Arementioning
confidence: 99%